Introduction: Centrifuge and Fragmentation - Helena Goscilo (Studies in 20th & 21st Century Literature, 2000)
The seismic changes inaugurated by desovietization not only recast the entire framework of Russia's cultural priorities, production, and reception, but ultimately revised fundamental concepts of what constitutes culture…
Keywords: fragmentation; desovietization; Russia; Russian culture; culture; economy; generes; pulp fiction; Postsoviet Russia; sex; sexualization; criminalization; machismo; stylization